LEVERAGING MIND MAPS FOR ELT: A SYSTEMATIC REVIEW - Syifa Nurhikmah Lestari; Nida Aida; Nafan Tarihoran (Integrative Perspectives of Social and Science Journal, 2025)
This systematic review examines the effectiveness of mind maps in English Language Teaching (ELT) by synthesising findings from 33 selected studies. Mind maps, as visual learning tools, have been widely recognised for enhancing students’ critical thinking, vocabulary acquisition, reading comprehension, and writing skills. This study follows the PRISMA framework to analyse research from various academic databases, including Mendeley, PubMed, Taylor & Francis, and Scopus, focusing on studies published between 2020 and 2024. The results indicate that mind maps facilitate knowledge retention, foster deeper conceptual understanding, and support collaborative learning. Additionally, when integrated with technology, digital mind maps enhance interactivity and student engagement in language learning. However, challenges such as teacher readiness and student adaptation to visual learning strategies remain significant concerns. The findings highlight the pedagogical implications of mind maps in ELT and recommend further exploration of their integration into digital learning environments.